Main trends in development and regulation of long-term bank lending in the Republic of Kazakhstan - Talimova, L.A.; Kalkabayeva, G.M.; Saifullina, Yu.M.; Kozlova , N.G. (BUKETOV BUSINESS REVIEW, 2019)
The article considers modern trends of long-term bank crediting of enterprises of the real sector of Kazakhstan’s economy. The main reasons for the low activity of second-tier banks in investment lending have been identified. The factors that had a negative impact on long-term loans of Kazakhstan banks provided to the real sector of the economy are justified. A comparative analysis of the proportion of long-term loans in GDP. The methods and tools of state regulation of the activities of second-tier banks on long-term lending to subjects of the real sector of the economy are systematized. One of the directions of the public economic policy is the regulation of investment activities of commercial banks, which is aimed, on the one hand, to contribute to the socio-economic development of the country, and on the other hand, to ensure the financial stability of the banking system as a whole and an appropriate level of protection of the interests of banking services’ consumers. The economic-mathematical model for forecasting the volume of long-term bank lending and the impact on them of macroeconomic regulation instruments in the Republic of Kazakhstan is presented. Measures to create conditions for the development of long-term bank lending are outlined.